2022
DOI: 10.1038/s41538-022-00174-y
|View full text |Cite
|
Sign up to set email alerts
|

Dietary inclusion of nitrite-containing frankfurter exacerbates colorectal cancer pathology and alters metabolism in APCmin mice

Abstract: Colorectal cancer (CRC) is the second most prevelant malignancy in Europe and diet is an important modifiable risk factor. Processed meat consumption, including meats with preservative salts such as sodium nitrite, have been implicated in CRC pathogenesis. This study investigated how the CRC pathology and metabolic status of adenomatous polyposis coli (APC) multiple intestinal neoplasia (min) mice was perturbed following 8 weeks of pork meat consumption. Dietary inclusions (15%) of either nitrite-free pork, ni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 41 publications
(43 reference statements)
1
5
0
Order By: Relevance
“…[39] MDF are proposed as cancer precursors and usable endpoints in short term carcinogenesis study with a good predictive character for tumor stage effects. [26] In this way, the very recent results of Crowe et al [40] confirmed our previous results at the tumor stage, by demonstrating also in Min mice that a nitrite-free sausage protects against promotion of intestinal tumors in comparison to nitrited ones. The results of our team, including the present study, and the results of Crowe et al support the role of nitrite salt food additive in colorectal cancer promotion associated to processed meat consumption.…”
Section: Discussionsupporting
confidence: 81%
“…[39] MDF are proposed as cancer precursors and usable endpoints in short term carcinogenesis study with a good predictive character for tumor stage effects. [26] In this way, the very recent results of Crowe et al [40] confirmed our previous results at the tumor stage, by demonstrating also in Min mice that a nitrite-free sausage protects against promotion of intestinal tumors in comparison to nitrited ones. The results of our team, including the present study, and the results of Crowe et al support the role of nitrite salt food additive in colorectal cancer promotion associated to processed meat consumption.…”
Section: Discussionsupporting
confidence: 81%
“…MDF are proposed as cancer precursors and usable endpoints in short term carcinogenesis study with a good predictive character for tumor stage effects 21 . In this way, the very recent results of Crowe et al 23 . confirmed our previous results at the tumor stage, by demonstrating also in Min mice that a nitrite-free sausage protects against promotion of intestinal tumors in comparison to nitrited ones.…”
Section: Discussionmentioning
confidence: 60%
“…This relationship between pickled foods and FGIDs has been rarely studied in previous research. Pickled foods are known to contain high levels of nitrite, and it has been observed that mice ingesting nitrite were more prone to developing intestinal flora disorders compared to those not ingesting nitrite 39 . This suggests that the pathogenesis of FGIDs caused by pickled foods may involve the disruption of intestinal flora, although further research is needed to confirm this hypothesis.…”
Section: Discussionmentioning
confidence: 99%